PERLINDUNGAN HUKUM TERHADAP INVESTOR/NASABAH YANG MENGALAMI KERUGIAN DALAM TRANSAKSI TRADING FOREX - Ivana Laura Paparang (Fakultas Hukum Universitas Pasundan, 2020)
Legal protection of investors/customers who conduct futures trading transactions include the rights and obligations of the Parties whether the customer is injured or the brokerage company that must fulfill responsibility due to the perceived loss of customers. This study used normative juridical library research method which describes the contracts stipulated in the LAW No. 10, 2011 and the unbalanced rules of the BAPPEBTI govern the rights and obligations of the parties. Therefore, this journal is about the protection of the law of customers who have suffered losses in forex transactions and the settlement of administrative, civil and criminal disputes in accordance with the guidelines of applicable legislation Keyword : Legal Protection,Trading Transactions, Investors/Consumers.